DEFINING NORMAL REFERENCE RANGE FOR THE CROSS-SECTIONAL AREA OF THE MEDIAN NERVE AT THE WRIST AND FOREARM USING HIGH-RESOLUTION ULTRASONOGRAPHY IN ASYMPTOMATIC PAKISTANI ADULTS - Rashed Nazer; Rauf, Maria; Farheen Raza; Balqees Yawar Fiaz; Madiha Saeed Wahla; Raheela Aqeel (Journal of Ayub Medical College Abbottabad, 2023)
Background: Carpal tunnel syndrome (CTS) can be diagnosed easily on ultrasonography (USG); which is a cheap, non-invasive and readily available modality. However, there is wide normal variation in the normal values of cross-sectional area (CSA) of median nerve among different populations; therefore, its necessary to establish a normal range of variability in median nerve dimensions in different populations. Method: A total of 500 asymptomatic patients i.e., 1000 median nerves were evaluated at the distal wrist crease and mid-forearm by 3 expert radiologists independently. All patients having a positive nerve conduction study or history of carpal tunnel syndrome and wrist trauma were excluded. Ultrasound was performed with a 7.5-15 MHz high-frequency linear probe. SPSS v 20 was used to analyze data. Results: the study population had a mean age of 31.40±10.11 years with a female-to-male ratio of 1.36:1. Mean BMI was 22.15±4.34 Kg/m2. The mean cross-section area of the median nerve at the right wrist was calculated to be 6.8±1.96 mm2 and the left wrist was 6.6±1.96 mm2. The mean median nerve cross-section area at the right mid-forearm was 5.3±1.46 mm2 and the left mid-forearm was 5.2±1.50 mm2. A decrease in mean median nerve cross-section areas was noted by moving from wrist to forearm. Similarly, males showed higher median nerve CSA than females. Conclusion: Mean median nerve cross-section area was found to be different from Western countries. This warrants the utilization of the data of the Pakistani population to establish our own normal reference range for median nerve cross-sectional area to avoid misdiagnoses.